Local Culture Influence in Javanese Advertising: A Cultural Linguistic Study - Kristianti, Tri; Balol, Wirawan Aryanto; Rokhmawati, Dian (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
As a medium of communication, language plays a significant role in translating two individuals’ thoughts and feelings. People feel comfortable sharing their interests when they use a common medium of language as a communication tool. Language and culture are inextricably linked, and they have correlatively integrated each other in certain aspects, such as the interaction between the cultures using the speaker’s language as a main means of communication. This study aims to investigate the correlation between culture and language in Javanese advertising viewing from the perspective of ethnolinguistic study. The descriptive qualitative is employed in this study using three phases of techniques: data collection, data analysis, and result presentation of data analysis. The result shows that local language influences the phrasings used in Javanese advertising creating an emotional bond between the product and consumers for several reasons: it helps them understand the message better, second, it increases their interest in the product, and third, it popularizes their local language.